Phylogenetic study documents different speciation mechanisms within the Russula globispora lineage in boreal and arctic environments of the Northern Hemisphere - Miroslav Caboň; Guo-Jie Li; Malka Saba; Miroslav Kolařík; Soňa Jančovičová; Abdul Nasir Khalid; Pierre-Arthur Moreau; Hua-An Wen; Donald H. Pfister; Slavomír Adamčík (IMA Fungus)
Abstract The Russula globispora lineage is a morphologically and phylogenetically well-defined group of ectomycorrhizal fungi occurring in various climatic areas. In this study we performed a multi-locus phylogenetic study based on collections from boreal, alpine and arctic habitats of Europe and Western North America, subalpine collections from the southeast Himalayas and collections from subtropical coniferous forests of Pakistan. European and North American collections are nearly identical and probably represent a single species named R. dryadicola distributed from the Alps to the Rocky Mountains. Collections from the southeast Himalayas belong to two distinct species: R. abbottabadensis sp. nov. from subtropical monodominant forests of Pinus roxburghii and R. tengii sp. nov. from subalpine mixed forests of Abies and Betula. The results suggest that speciation in this group is driven by a climate disjunction and adaptation rather than a host switch and geographical distance.